LIM-domain binding protein 2 was down-regulated by miRNA-96-5p inhibited the proliferation, invasion and metastasis of lung cancer H1299 cells - Chu, Fuying; Xu, Xinxin; Zhang, Yan; Cai, Hua; Peng, Jingjing; Li, Yanan; Zhang, Han; Liu, Hongli; Chen, Xiang (Clinics, 2022)
Objectives: Lung cancer was one of the most common malignancies around the world. It has great significance in to search for the mechanism of occurrence and development of lung cancer. LIM Domain Binding protein 2 (LDB2) belongs to the LIM-domain binding family, it can be used as a binding protein that combined with other transcription factors to form the transcription complex for regulating the expression of target genes. The expression of microRNA-96-5p (miR-96-5p) has been investigated in various tumors. The aim of this study is to investigate the potential role of LDB2 and miR-96-5p in lung cancer. Methods: Real-time quantitative PCR was applied to detect the expression of LDB2 and miR-96-5p. The proliferation, invasion, and metastasis of H1299 cells were analyzed by CCK8, transwell, and wound healing assay after LDB2 or miR-96-5p transfection. Luciferase activities assay and western blot were used to reveal the targeted regulation between LDB2 and miR-96-5p. Results: Here the authors found LDB2 was down-regulated in lung cancer tissues and negatively correlated with miR-96-5p expression, it could promote or inhibit the proliferation, invasion and metastasis of H1299 cells after LDB2 knockdown or overexpression and regulate the expression of cyclinD1, MMP9, Bcl-2, and Bax via ERK1/2 signaling pathway. Furthermore, miR-96-5p exerted its function by directly binding to 3′-UTR of LDB2 and regulating expression of LDB2. miR-96-5p could promote the proliferation, invasion, and metastasis of H1299 cells. Conclusion: These findings demonstrate that LDB2 can act as a new regulator to inhibit cell proliferation, invasion, and metastasis via the ERK1/2 signaling pathway, and miR-96-5p may be a potential promising molecular by targeting LDB2 in lung cancer.